TINJAUAN LITERATUR SISTEMATIS: ANALISIS KINERJA LALU LINTAS PADA FASILITAS U-TURN - Yusra Aulia Sari; Ardhela Sukeysih; Joewono Prasetijo (CRANE: Civil Engineering Research Journal, 2026)
U-turn facilities are an important element in road networks that serve to facilitate changes in vehicle direction. However, incorrect placement often causes traffic congestion, reduces vehicle speed, and increases waiting times. This study was conducted to analyse the effect of U-turn facility design and layout on traffic flow performance using the SLR method with the PRISMA protocol. Data were collected from several scientific journals indexed by PoP and VOSviewer, then selected based on relevance, year of publication, and contextual suitability. The review results show that conventional U-turn designs tend to cause conflicts in main road traffic, while the use of alternative designs, such as RCUT and P-MUT has been proven to improve vehicle flow efficiency, reduce delays, and increase road service levels. This study is expected to recommend more effective and safer U-turn geometric designs for implementation in areas with high traffic volumes, thereby improving the overall performance of urban transportation networks.